IMPLEMENTASI PRINSIP REWARD DAN PUNISHMENT DALAM MENINGKATKAN MOTIVASI BELAJAR MENGAJI SANTRI TPQ BABURRAHMAH - Basy, Bashiratud Diyana; Basir, Abdul (IAI DARUL ULUM KANDANGAN, 2025)
Quranic education in non-formal institutions such as the Taman Pendidikan Al-Qur'an (TPQ) faces complex challenges, particularly regarding the heterogeneity of students' ages in a single class, ranging from early childhood (PAUD) to adolescence (junior high school). This condition leads to variations in cognitive abilities and concentration levels, complicating classroom management and the maintenance of learning motivation. This study aims to analyze teachers' strategies in bridging these challenges through the implementation of reward and punishment methods, focusing on their forms, processes, impacts, and effectiveness on students' motivation and learning achievement. This study employs a qualitative field research approach at TPQ Baburrahmah, Banjarbaru. Data collection was conducted through in-depth interviews with 10 key informants (teachers) and literature review. The results indicate that: (1) Forms of reward are dominated by verbal praise and body gestures as positive reinforcement, while punishment is applied persuasively through verbal admonition without physical violence; (2) The implementation process is based on the principles of balance (Law of Effect), immediacy, and a humanist approach; (3) The impact of implementation proves to be constructive, where rewards fulfill Esteem Needs and punishment builds inner control. This strategy is considered highly effective in improving learning achievement through the